Ensuring Information Integrity in a Mobile-Connected World - Neoaz, Nahid; Amin, Mohammad Hasan (Information Technology and Science (ITScience), 2024)
The sunlight adoption of portable devices in individual and business activity has made a higher urgency of appropriate mobile information assurance policies. This article explores key approaches to securing mobile devices and sensitive information, focusing on three major components: Mobile Device Management (MDM), mobile security best practices, mobile cloud computing. MDM solutions are ways through which organizations can gain control in mobile devices with secure policies, distant management, and compliance checks. In addition, best practices for the physical security of mobiles, which include the use of non-disclosed passwords, the enabling of the encrypt or and the use of virtual private networks or other such security tools go further in safeguarding mobile environments against elements like malware and intrusion. Besides, cloud computing supports portable information assurance by providing backup, recovery, and security measures like encryption, and ID confirmation. Solutions based on cloud technology allow to implement effective data sharing and processing, as well as to control data security and compliance with the requirements of existing legislation. Altogether, these measures constitute an integrated security strategy of mobile, it provides protection to sensitive data, makes them accessible, and help in managing or eradicating threats in the connected environment.